2018
DOI: 10.3390/fib6030062
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Absorption and Opacity of Starch-Based Biocomposites Reinforced with Cellulose Fiber from Bengkoang

Abstract: Cellulose fiber was isolated from bengkoang (Pachyrhizus erosus) tuber peel. A suspension consisting of distilled water, starch, and glycerol was mixed with various cellulose loadings (0, 2, 6, and 10 g) then gelatinized using a hot plate with a magnetic stirrer. The biocomposite gel was sonicated using an ultrasonication probe (47.78 W/cm2 for 4 min). Scanning electron microscopy (SEM) micrographs for the fracture surface of resulting biocomposite films displayed a rougher surface than starch film, indicating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Starch is widely available (from rice, potato, wheat, corn, and certain plant roots), cheap, and biodegradable. Starch is also very hydrophilic and, thus, absorbs water readily, followed by rapid degradation. , TENG performance depends greatly on the active material; the hydrophilicity of pristine starch renders its use problematic. ,, Here, we enhanced the hydrophilicity of edible corn starch when fabricating starch/Laver TENGs (SL-TENGs). Laver is an edible Korean seaweed.…”
Section: Introductionmentioning
confidence: 99%
“…Starch is widely available (from rice, potato, wheat, corn, and certain plant roots), cheap, and biodegradable. Starch is also very hydrophilic and, thus, absorbs water readily, followed by rapid degradation. , TENG performance depends greatly on the active material; the hydrophilicity of pristine starch renders its use problematic. ,, Here, we enhanced the hydrophilicity of edible corn starch when fabricating starch/Laver TENGs (SL-TENGs). Laver is an edible Korean seaweed.…”
Section: Introductionmentioning
confidence: 99%
“…The FTIR spectra showed a lower transmittance at –OH stretching in the CMC/PSO films because of the hydrophobic nature of the CMC film. Two distinctive peaks appeared at around 2950–2905 cm −1 in all films, corresponding to –CH stretching (Hafizulhaq et al, 2018). The peak at around 1750 cm −1 in CMC/PSO‐2 and CMC/PSO‐3 was higher than the CMC which indicates carbonyl‐stretching vibration in the ester group.…”
Section: Resultsmentioning
confidence: 92%
“…The peak at 1600 cm −1 due to the –COO– asymmetric stretching vibration (Liu et al, 2017) was not observed in the CMC/PSO‐3 film. Other bands were visible around 1430, 1340, and 1054 cm −1 , which indicates the –CH 2 –(C 6 )– bending vibration, –CO stretching in an aryl‐alkyl ether, and C–O stretching for the ether group (CH–O–CH 2 ) (Hafizulhaq et al, 2018; Moganavally et al, 2016; Samsi et al, 2019), respectively, for the CMC film. The increase in the PSO volume added to the CMC solution has significantly reduced the intensity of these peaks.…”
Section: Resultsmentioning
confidence: 99%
“…Vinyl ester and polyester‐based composite exhibiting a compact intermolecular structure based on the curing temperature, which effectively lowered the diffusion coefficient compared to polyester matrix. [ 135 ] The influence of moisture absorption and opacity on starch‐based biopolymers reinforced with cellulose from Bengkoang is investigated by Hafizulhaq et al [ 136 ] The inclusion of cellulose improves the moisture resistance and opacity of films. The biocomposite had a moisture absorption rate of 16.79% inferior than the starch films.…”
Section: Moisture Absorption Testmentioning
confidence: 99%